My 28 Days - a global digital women’s health initiative for evaluation and management of secondary amenorrhea: case report and literature review - Nelson, Lawrence M.; Spencer, Hillary; Hijane, Karima; Thinuan, Payom; Nelson, Chaninan W.; Vincent, Amanda J.; Gordon, Catherine M.; Plant, Tony M.; Fazeli, Pouneh K. (Frontiers in Endocrinology, 2023)
There is a need to close the gap between knowledge and action in health care. Effective care requires a convenient and reliable distribution process. As global internet and mobile communication increase capacity, innovative approaches to digital health education platforms and care delivery are feasible. We report the case of a young African woman who developed acute secondary amenorrhea at age 18. Subsequently, she experienced a 10-year delay in the diagnosis of the underlying cause. A global digital medical hub focused on women's health and secondary amenorrhea could reduce the chance of such mismanagement. Such a hub would establish more efficient information integration and exchange processes to better serve patients, family caregivers, health care providers, and investigators. Here, we show proof of concept for a global digital medical hub for women's health. First, we describe the physiological control systems that govern the normal menstrual cycle, and review the pathophysiology and management of secondary amenorrhea. The symptom may lead to broad and profound health implications for the patient and extended family members. In specific situations, there may be significant morbidity related to estradiol deficiency: (1) reduced bone mineral density, 2) cardiovascular disease, and 3) cognitive decline. The Mary Elizabeth Conover Foundation has addressed the specific global educational needs of women with a condition known as primary ovarian insufficiency (POI). The Foundation created a professionally managed Facebook group for these women. POI most commonly presents with secondary amenorrhea. Anatural history study on secondary amenorrhea with international reach can be coordinated by a global digital medical hub. Such an approach takes full advantage of internet and mobile device communication systems. We refer to this global digital women's health initiative as My 28 Days.